Mangroves Response to Climate Change: A Review of Recent Findings on Mangrove Extension and Distribution - Mario D.P. Godoy; Luiz D. de Lacerda (Anais da Academia Brasileira de Ciências, 2015)
Mangroves function as a natural coastline protection for erosion and inundation, providing important environmental services. Due to their geographical distribution at the continent-ocean interface, the mangrove habitat may suffer heavy impacts from global climate change, maximized by local human activities occurring in a given coastal region. This review analyzed the literature published over the last 25 years, on the documented response of mangroves to environmental change caused by global climate change, taking into consideration 104 case studies and predictive modeling, worldwide. Most studies appeared after the year 2000, as a response to the 1997 IPCC report. Although many reports showed that the world's mangrove area is decreasing due to direct anthropogenic pressure, several others, however, showed that in a variety of habitats mangroves are expanding as a response to global climate change. Worldwide, pole ward migration is extending the latitudinal limits of mangroves due to warmer winters and decreasing the frequency of extreme low temperatures, whereas in low-lying coastal plains, mangroves are migrating landward due to sea level rise, as demonstrated for the NE Brazilian coast. Taking into consideration climate change alone, mangroves in most areas will display a positive response. In some areas however, such as low-lying oceanic islands, such as in the Pacific and the Caribbean, and constrained coastlines, such as the SE Brazilian coast, mangroves will most probably not survive.